Penerapan Video Animasi 3D Sebagai Media Edukasi Pentingnya Menjaga Kesehatan di Era Endemi - Dalimunthe, Khairunnisa; Asih, Munjiat Setiani; khairunnisa, Khairunnisa (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
Coronavirus Disease 2019 (Covid-19) is a virus that can infect breathing ranging from mild symptoms to severe symptoms. Covid-19 is transmitted very quickly and spreads to almost all countries, one of which is Indonesia. The author finds a problem in the community environment, namely the lack of awareness and understanding of the importance of maintaining health in the endemic era. The public needs to know how to prevent the Covid-19 virus, the impacts and symptoms caused by Covid-19, and know solutions to overcome Covid-19 to avoid this dangerous virus. Educational media made in the form of 3D animated videos is thought to help people receive information more effectively and can apply it to their daily lives.